Inter-individual differences in within-person effects: methodological considerations and an empirical example in the framework of self-determination theory - Neubauer, Andreas B. (2017)
The increasing popularity of intensive longitudinal designs has also spawned an interest in the analysis of inter-individual differences in within-person effects. The aim of the present thesis was twofold: First, boundary conditions necessary to use estimates of inter-individual differences in within-person effects as predictors for future behavior were explored. Results from two simulation studies showed that under optimistic, but realistic conditions, these parameters can be assessed with sufficient reliability. The second aim was to investigate whether meaningful inter-individual differences in the within-person effect of competence fulfillment on well-being exist. Self-Determination Theory (SDT), a prominent theory in the realm of social-motivational psychology, proposes that such differences should be negligible, but a robust investigation from a within-person perspective has been missing. Findings from an initial set of studies showed that competence fulfillment should not be considered a one-dimensional construct, but competence satisfaction and dissatisfaction should be considered somewhat orthogonal constructs. Using a daily diary study, it was shown that there were inter-individual differences in the within-person association of both competence satisfaction and competence dissatisfaction with well-being (coined competence satisfaction strength, CSS, and competence dissatisfaction strength, CDS, respectively). In the final study of the present dissertation, an integrative study combining a daily diary part and an experimental part showed that the interaction of CSS and CDS moderated the effect of an experimentally induced frustration of the need for competence on negative affect: Individuals who reacted particularly strong towards daily competence dissatisfaction and who reacted less strong towards daily competence satisfaction were most strongly affected by an experimentally induced frustration of the need for competence. These findings challenge SDT’s universality assumption of the need for competence. The dissociation into competence satisfaction and competence dissatisfaction lends further support to a two-process model of need fulfillment that is used as a basis for a dynamic model of need fulfillment that is proposed in the final part of this dissertation.
Keywords: Hochschulschrift; Theorie; Selbstbestimmungsrecht